The Impact of Transculturality on Student Experience of Higher Education. (March 2018) - Smith, Heidi A.; Segbers, Teresa
Background: Higher education outdoor studies programs retain a critical interest in student experiences as they seek to prepare citizens in a globalized, yet simultaneously neo-nationalist, world.Purpose: This research explored the impact of transculturality on the student experience of outdoor studies in the Transcultural European Outdoor Studies (TEOS) Masters, a course hosted by three universities in three countries.Methodology/Approach: A longitudinal study of the student experience, using a conceptual framework of self, place, transculturality, and outdoor learning theory underpins the research. Semistructured online interviews and one face-to-face retrospective interview were conducted with four participants throughout the course (Semesters 1, 2, 3), plus an additional five participants prior to the end of Semester 3.Findings/Conclusions: The findings elucidate students' transcultural self-growth and transcultural capabilities, including resilience, intelligence, and fatigue.Implications: Although challenges exist for course design, considerations of transcultural pedagogy and curricula, reflective practices, support for students and teaching staff, cultural learning experiences (including language acquisition), and a willingness to move beyond traditional models of curricula at the university level are recommended.